Chemopreventive efficacy of raloxifene, bexarotene and their combination on the progression of chemically-induced colon adenomas to adenocarcinomas in rats - Janakiram, Naveena B. (Cancer Prev Res (Phila), 2013)
Estrogen Receptor (ER)-β signaling is associated positively in colon tumor progression, whereas down-regulation or loss of function of retinoid X receptor (RXR)-α occurs in colon tumors. The chemopreventive efficacies of the estrogen antagonist raloxifene and the selective RXR agonist bexarotene were tested individually and in combination, during promotion and progression stages of colon tumorigenesis. Colon tumors were induced in male F344 rats with azoxymethane and at early adenoma stage, groups of rats (36 or 45/group) were fed diets containing raloxifene (1.5 or 3 ppm), bexarotene (50 or 100 ppm), or their low dose combinations for 40 weeks. Raloxifene or bexarotene alone significantly suppressed colon adenocarcinoma formation in terms of multiplicities (mean ± SE): control, 3.59 ± 0.25; 1.5 ppm raloxifene, 2.51 ± 0.29 (p<0.004); 3 ppm raloxifene, 2.14 ± 0.28 (p<0. 0001); 50 ppm bexarotene, 2.25 ± 0.32 (p<0.001); 100 ppm bexarotene, 2.1 ± 0.27 (p<0.0001) and 1.5 ppm raloxifene + 50 ppm bexarotene, 1.57 ± 0.21 (p<0.0001). The low dose combination caused significant (56 %) inhibition of adenocarcinomas as compared with control diet fed rats. Tumors exposed to raloxifene, bexarotene and/or the combination showed significant suppression of proliferating cell nuclear antigen, cyclin D1 and β-catenin with an increased apoptotic cells (3-fold) and p21 expression (3.8-fold) as compared tumors of rats fed control diet. The combination of low doses of raloxifene and bexarotene significantly suppressed the progression of colonic adenomas to adenocarcinomas and may be useful for colon cancer prevention and/or treatment in high-risk individuals.